Two Decades of Research on Geometry Education in Ibero-America: An Exploratory Systematic Review - Vargas Herrera, Juan Pablo (2025)
Recent studies on the development of strategies and proposals to enhance geometric thinking reflect the advancement of Geometry Education as a research field. The identification of key areas of interest and thematic lines also helps to reveal significant gaps that hinder improvements in the teaching and learning of geometry. [Objective] This article is intended to carry out an exploratory systematic review of literature published in high-impact journals in Ibero-America to identify the main research focus in geometry education during the first decades of the 21st century. [Methodology] The review is organized into three phases: selection, descriptive analysis, and interpretation. In the first phase, the selected articles are characterized according to variables such as type of study, educational level, participant profile, and implementation modality. In the second phase, nine emerging categories are identified and subsequently organized into four overarching analytical categories. [Results] The findings partially align with those reported in other systematic reviews, highlighting interest in the design and use of tasks, mathematical processes, the role of technology, and the analysis of errors and learning obstacles. However, the review also reveals a limited number of studies addressing mathematical connections, teacher-student interaction, the impact of contextual conditions, and the use of evaluation results to inform pedagogical decision-making. [Conclusions] This review contributes to updating the landscape of research in geometry education, identifying consolidated lines of inquiry and highlighting strategic gaps to guide future research agendas.